Development of seasoned green mussel (Perna viridis) with sodium reduction using stealth reduction approaches - Passakorn Kingwascharapong; Jarupat Janthueng; Peeraya Kongsorn; Sasina Sanprasert; Nantipa Pansawat; Nawaporn Wannawisan; Kanrawee Hunsakul; Ali Muhammed Moula Ali; Lutz Grossmann; Samart Sai-ut; Jaksuma Pongsetkul; Suphat Phongthai; et al. (Future Foods)
Excessive levels of sodium consumption over the recommended human daily intake level is a global issue. Developing novel low-sodium products to address this issue is challenging. Moreover, there is little research on the use of stealth reduction approaches in reduced sodium seasoned green mussel, representing an additional opportunity for advancement in developing novel products in the seafood processing industry. Thus, this study aimed to develop a seasoned green mussel (Perna viridis) product with a reduced sodium content. The study consisted of two parts: The first part studied two types mussel seasonings (‘Pad-char’; PC and ‘Prik-Pao’; PP) with various sodium reduction levels (30, 70, or 100 %). The difference in taste profiles was confirmed using an electronic tongue technique and consumer acceptance trial. Green mussels seasoned with PC were preferred over those seasoned with PP. Green mussels seasoned with PC at a 30 % sodium reduction level (PC-30 %) received the second highest overall liking score, following the standard, and had a sodium content of 623.80 mg/100 g. Furthermore, PC-30 % was rich in other essential nutrients such as protein and vitamin A. The second aim was to study the shelf-life of the PC-30 % products with storage at 4 ± 1ºC for 12 days. During storage, the PC-30 % sample developed a tough texture, as indicated by higher hardness and chewiness values, along with increased pH and total volatile-based nitrogen. The microbial loads indicated that the shelf-life of the PC-30 % product stored at 4 ± 1ºC was 9 days. This suggests that reducing sodium in mussels through seasoning is feasible while maintaining acceptable sensory scores, but shelf-life challenges must be addressed before bringing these products to market.